A controlled study to assess the effects of a Fast Track (FT) service delivery model among stable HIV patients in Lusaka Zambia. - Carolyn Bolton Moore; Jake M Pry; Mpande Mukumbwa-Mwenechanya; Ingrid Eshun-Wilson; Stephanie Topp; Chanda Mwamba; Monika Roy; Hojoon Sohn; David W Dowdy; Nancy Padian; Charles B Holmes; Elvin H Geng; et al. (Public Library of Science (PLoS), 2022)
Fast Track models-in which patients coming to facility to pick up medications minimize waiting times through foregoing clinical review and collecting pre-packaged medications-present a potential strategy to reduce the burden of treatment. We examine effects of a Fast Track model (FT) in a real-world clinical HIV treatment program on retention to care comparing two clinics initiating FT care to five similar (in size and health care level), standard of care clinics in Zambia. Within each clinic, we selected a systematic sample of patients meeting FT eligibility to follow prospectively for retention using both electronic medical records as well as targeted chart review. We used a variety of methods including Kaplan Meier (KM) stratified by FT, to compare time to first late pick up, exploring late thresholds at >7, >14 and >28 days, Cox proportional hazards to describe associations between FT and late pick up, and linear mixed effects regression to assess the association of FT with medication possession ratio. A total of 905 participants were enrolled with a median age of 40 years (interquartile range [IQR]: 34-46 years), 67.1% were female, median CD4 count was 499 cells/mm3 (IQR: 354-691), and median time on ART was 5 years (IQR: 3-7). During the one-year follow-up period FT participants had a significantly reduced cumulative incidence of being >7 days late for ART pick-up (0.36, 95% confidence interval [CI]: 0.31-0.41) compared to control participants (0.66; 95% CI: 0.57-0.65). This trend held for >28 days late for ART pick-up appointments, at 23% (95% CI: 18%-28%) among intervention participants and 54% (95% CI: 47%-61%) among control participants. FT models significantly improved timely ART pick up among study participants. The apparent synergistic relationship between refill time and other elements of the FT suggest that FT may enhance the effects of extending visit spacing/multi-month scripting alone. ClinicalTrials.gov Identifier: NCT02776254 https://clinicaltrials.gov/ct2/show/NCT02776254.